Determining the style and provenance of magmatic activity during the Early Aptian Oceanic Anoxic Event (OAE 1a) - Percival, LME; Tedeschi, LR; Creaser, RA; Mather, TA; Jenkyns, HC; Et al. (Elsevier, 2021)
Large igneous province (LIP) volcanism has been proposed as a key trigger of several major climate and environmental perturbations during the Phanerozoic Aeon. Large-scale carbon emissions associated with one or both of magmatic degassing from the Greater Ontong Java Plateau (G-OJP) and intrusion of organic-rich sediments by High Arctic LIP (HALIP) sills have been widely suggested as the trigger of the Early Aptian Oceanic Anoxic Event (OAE 1a: ~120 Ma). However, the respective roles of the two LIPs and associated carbon sources in causing this crisis remain debated. Here, six records of OAE 1a from the Pacific, Tethyan, Arctic, and South Atlantic realms are investigated, combining mercury (Hg) concentrations and osmium (Os-) isotope ratios as proxies of LIP activity. Together with previously published datasets, the results indicate globally consistent Os-isotope evidence for LIP activity during OAE 1a, but geographically variable stratigraphic Hg trends. Clear mercury enrichments that match Os isotope evidence of LIP activity, and suggest a Hg-cycle perturbation during the onset of OAE 1a, are documented at one Pacific site extremely proximal to the G-OJP, but not in Arctic, Tethyan or Atlantic records. This pattern highlights significant G-OJP volcanism during the onset of OAE 1a, and re-emphasises the limited potential for submarine LIP eruptions to cause Hg-cycle perturbations except in areas very proximal to source. The absence of clear Hg peaks in basal OAE 1a strata from the Arctic (or anywhere outside of the Pacific) does not support intense HALIP activity at that time, suggesting that the G-OJP was the more volcanically active LIP when OAE 1a commenced. Thus, G-OJP emissions of mantle carbon were more likely to have played a major role in initiating OAE 1a than thermogenic volatiles associated with the HALIP. A transient pulse of HALIP-related subaerial eruptions and/or thermogenic volatile emissions during the early–middle part of OAE 1a, potentially evidenced by more widespread Hg enrichments in strata from that time (including in the Arctic), might have prolonged the event. However, a non-volcanic cause of these later Hg influxes cannot be excluded. These findings challenge previous suggestions that magmatic CO2 emissions from LIPs were incapable of causing major carbon-cycle perturbations alone, and highlight the need for further investigations to establish whether the high volume/emplacement rate of the G-OJP (potentially an order of magnitude greater than other LIPs) made it a unique case that stands in contrast to other provinces where the role of thermogenic volatiles was likely more crucial.